Mapping between space-like curve flows and soliton equations in Minkowski space - Yüzbaşl, Zühal Küçükarslan; Yoon, Dae Won; Myrzakulov, Ratbay (World Scientific, 2024)
In this study, we demonstrate that when three distinct moving space-like curves with the time-like binormal vectors satisfy the generalizations of the Heisenberg spin chain model, these models are equivalent to the third-order system of the AKNS hierarchy and the complex KdV-type equations. © 2024 World Scientific Publishing Company.
Keywords: AKNS hierarchy; complex KdV; Hasimoto map; Heisenberg spin chain model